2007
DOI: 10.1038/sj.mt.6300033
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Collection and Gene Transfer in Fanconi Anemia

Abstract: Fanconi anemia (FA) is a rare genetic syndrome characterized by progressive bone marrow failure (BMF), congenital anomalies, and a predisposition to malignancy. Successful gene transfer into hematopoietic stem cells (HSCs) could reverse BMF in this disease. We developed clinical trials to determine whether a sufficient number of CD34(+) stem cells could be collected for gene modification and to evaluate the safety and efficacy of HSC-corrective gene transfer in FA genotype A (FANCA) patients. Here, we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(126 citation statements)
references
References 43 publications
2
117
1
6
Order By: Relevance
“…To overcome these limitations, FA gene therapy clinical trials are in progress [85]. Difficulties in collecting sufficient blood progenitor cells from patients with FA and inefficient transduction protocols with first-generation retroviral vectors led to unsuccessful initial clinical trials [86][87][88].…”
Section: Novel Therapies: From Genes To Patientsmentioning
confidence: 99%
“…To overcome these limitations, FA gene therapy clinical trials are in progress [85]. Difficulties in collecting sufficient blood progenitor cells from patients with FA and inefficient transduction protocols with first-generation retroviral vectors led to unsuccessful initial clinical trials [86][87][88].…”
Section: Novel Therapies: From Genes To Patientsmentioning
confidence: 99%
“…Clinical trials using gene-modified hematopoietic stem cells have been undertaken to assess treatment of a number of Integration of a genomic locus into human stem cells F Zaibak et al hematological conditions. [22][23][24][25][26][27][28] Recent preclinical studies using in vitro cultured gene-modified mesenchymal stem cells have also shown promise. [29][30][31][32][33] However, in the majority of these studies, which use viral delivery of small vectors, random integration at multiple sites per cell and different sites between cells was documented, along with variegated expression and transcriptional silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Основной про-блемой данного подхода явилось то, что эффективность трансфекции гемопоэтических стволовых клеток ре-тровирусным вектором, содержащим нативный ген, была низкой и недостаточной для значимого улучше-ния гемопоэза [11]. Недавно было опубликовано не-сколько исследований [12,13], основным вопросом которых явился поиск оптимального клеточного суб-страта для воздействия.…”
Section: факторы ростаunclassified